Comparative Analysis Of The Altman, Ohlson, And Zmijewski Models To Predict Financial Distress During The Covid-19 Pandemic - Nurilen Wuri Santoso; Ratih Kusumawardhani; Alfiatul Maulida (Universitas Muhammadiyah Semarang, 2024)
This study analyses financial distress predictions by comparing modified Altman Z-Score, Ohlson O-Score, and Zmijewski X-Score models (Case Study of Companies in the Transportation and Logistics Sector for the 2019-2021 Period). The population in this study is represented by transportation and logistics companies listed on the IDX. The sample collection technique in this study utilizes purposive sampling techniques using predetermined parameters, and as many as 23 companies were obtained as samples. The data used in this study was taken from the company's transportation and logistics financial statements. This research utilizes descriptive statistical tests, normality tests, and accuracy tests of prediction models as hypothesis tests. The results of this study show that the modified Altman Z-Score model is the most accurate model, with an accuracy level of 68.12%.